Síntese e avaliação da atividade antimicobacteriana de 3-Aril-1-H-indóis : protótipos para o desenvolvimento de candidatos à fármacos para o tratamento da tuberculose - Etchart, Renata Jardim (2021)
Pulmonary tuberculosis occurs through airborne transmission and shows diversity in clinical manifestations. The extent of the infection depends on the host's immune response, culminate in cure, progression to the latent or active form of the disease. In 2019, it was estimated at 10 million (8.9 - 11.0 million) the number of new tuberculosis (TB) cases in the world. In Brazil, about 4,500 deaths from the disease were reported. In 1993, WHO established tuberculosis as a public health emergency and a therapeutic strategy of Directly Observed Treatment Short-course (DOTS) was fundamental to progress in combating the disease. Although the total number of deaths has decreased, tuberculosis has prolonged as one of the ten leading causes of death in the world, mainly aggravated by co-infection with HIV, the growing number of cases of resistant strains and, recently, by the COVID-19 pandemic. Despite the existence of a vaccine, such as BCG, pharmacotherapy is the most effective way of tuberculosis treatment. To achieve control of this TB epidemic, there is an urgent need for new anti-TB drugs and among the desired characteristics for these structures are low cost and easy administration, to ensure wide accessibility and adherence to treatment. Within this scenario, heterocycle chemistry is one of the most valuable sources of new compounds with diverse pharmacological activity, mainly because of the unique ability of constituted compounds to mimic the structure of peptides and reversibly bind to proteins. Almost limitless combinations of fused heterocyclic structures can be designed, updated into molecules with diverse physical-bonded, steric and electronic properties. Among the structures, the indole ring is one of the most studied compounds as a component of biologically active products. Due to its wide range of pharmacological activities, it is a privileged structure in medicinal chemistry. In this work, 3-aryl-1H-indoles were synthesized and their antimycobacterial activity determined. The compounds demonstrated activity against M. tuberculosis H37Rv strain and, the hit compounds, demonstrated activity against clinical MDR isolates. One of the hit compounds did not significantly affect the viability of the cell lines tested and did not produce DNA damage. To assess the dynamics of antimycobacterial activity, was performed a time-kill curve of compound 3r, combined with mathematical modeling to predict its pharmacodynamic characteristics. The minimum bactericidal concentration obtained was 2X MIC and the demonstrated kill kinetics were time-dependent, with characteristics similar to rifampicin. The results obtained in this work suggest that this class of molecules is promising and may lead to new anti-TB drug candidates.